Religious Moderation as a Pillar of Social Peace: Its Impact on the Development of Inclusive Social Policies in Religiously Diverse Countries - Haq, Saipul (Forum Akademisi dan Dosen Peneliti (FAST), 2025)
Religious moderation plays a crucial role in strengthening inclusive social policies and fostering sustainable social peace, especially in countries with high religious diversity such as Indonesia, India, and Nigeria. These nations face challenges of social tension, religious discrimination, and interfaith conflicts, arising from religious and ethnic differences. Religious moderation, as a strategy, emphasizes values of tolerance, respect for diversity, and interfaith dialogue, which serves to mitigate extremism and create harmonious coexistence among various religious groups. This study utilizes a qualitative approach with case studies to examine the impact of religious moderation on the development of inclusive social policies in these diverse countries. Key findings suggest that religious moderation within social policies can reduce religious discrimination, promote equality, and strengthen social cohesion. However, challenges such as economic disparities, social tensions, and the rise of religious extremism still pose significant barriers to the effective implementation of these policies. The research provides recommendations for policymakers to integrate religious moderation more thoroughly into inclusive social policies, focusing on education, religious leader training, and interfaith cooperation as essential elements. By promoting moderate religious values and fostering mutual respect, countries can move toward a more inclusive, just, and peaceful society. The study highlights that consistent and comprehensive application of religious moderation can address the root causes of religious conflict and strengthen social integration in pluralistic societies